Design and properties research of capacitive RF-MEMS switch. (1st January 2012) - Guo, Hai; Yin, Jinghua; Song, Mingxin; Zhao, Jingying
Three structures of capacitive RF-switches are presented, which are stimulated by the software, and the influences of the switch structure parameters on the driven voltage and nature frequency are studied respectively. Based on the research of the stimulation and analysis, the driven voltage value of the straight beam type switch is bigger than the cable-stayed and the bending beam type switches. But the straight beam has the bigger nature frequency. Cable stayed and the bending beam type switches have a small elastic constant, which results in a small driven voltage value.